2016
DOI: 10.1016/j.fertnstert.2016.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Influence of increasing body mass index on semen and reproductive hormonal parameters in a multi-institutional cohort of subfertile men

Abstract: In one of the largest cohorts of male fertility and obesity, serum hormone and semen parameters demonstrated mild but significant relationships with BMI, possibly contributing to subfertility in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
96
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 38 publications
12
96
0
1
Order By: Relevance
“…We also found that for couples undergoing oocyte retrieval cycles for TESA‐ICSI, male BMI was negatively associated with serum T levels and positively associated with E2 levels in males, consistent with several prior studies showing that obesity affects hormone levels in men of reproductive age (Jensen et al, ; MacDonald et al, ; Tunc et al, ). Systemic T is generally aromatised to E2 in adipose cells (Bieniek et al, ); therefore, increased E2 levels are observed in some obese men. E2 forms a negative feedback loop with the pituitary gland in the hypothalamic–pituitary–gonadal axis and probably leads to reduced T levels following lower LH secretion (Pavlovich, King, Goldstein, & Schlegel, ).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that for couples undergoing oocyte retrieval cycles for TESA‐ICSI, male BMI was negatively associated with serum T levels and positively associated with E2 levels in males, consistent with several prior studies showing that obesity affects hormone levels in men of reproductive age (Jensen et al, ; MacDonald et al, ; Tunc et al, ). Systemic T is generally aromatised to E2 in adipose cells (Bieniek et al, ); therefore, increased E2 levels are observed in some obese men. E2 forms a negative feedback loop with the pituitary gland in the hypothalamic–pituitary–gonadal axis and probably leads to reduced T levels following lower LH secretion (Pavlovich, King, Goldstein, & Schlegel, ).…”
Section: Discussionmentioning
confidence: 99%
“…Leptin-deficient mice have central hypogonadism and hence show reduced fertility. Low sperm counts and reduced sperm function have been reported in obese men [82]. Adipocytokines and inflammatory cytokines have all been shown to impact reproductive function and directly interact with the male reproductive system [83].…”
Section: Obesity and Pubertal Onset And Progressionmentioning
confidence: 99%
“…Nevertheless, the studies addressing specific relationships between semen parameters and obesity have yielded contradictory results. Although some recent data suggest a correlation between the increase in obesity and a reduction in sperm concentration, motility and/or morphology (Alshahrani, Ahmed, Gabr, Abalhassan, & Ahmad, ; Belloc et al., ; Bieniek et al., ; Dupont et al., ; Eisenberg et al., ; Luque et al., ; MacDonald, Stewart, & Farquhar, ; Taha et al., ; Umul et al., ), other studies did not detect statistically significant adverse effects of obesity on semen quality (Bandel et al., ; Thomsen, Humaidan, Bungum, & Bungum, ). Although three meta‐analyses were published, the contradictions remain.…”
Section: Introductionmentioning
confidence: 98%